2009
DOI: 10.1002/pmic.200900080
|View full text |Cite
|
Sign up to set email alerts
|

Early activation of the fatty acid metabolism pathway by chronic high glucose exposure in rat insulin secretory β‐cells

Abstract: Pancreatic beta-cells are responsible for insulin secretion that regulates blood glucose homeostasis. In the development of type II diabetes, a progressive impairment of insulin secretion by the pancreatic beta-cells occurs called beta-cell dysfunction or beta-cell failure. Chronic hyperglycemia has been shown being involved in beta-cell dysfunction, a phenomenon known as glucotoxicity. The molecular mechanisms underlying the impairment of insulin secretion by beta-cells induced by glucotoxicity are still not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…38 We observed that % tail DNA significantly increased in hyperglycemia treated 1.1B4 cells, which is similar to observations with RINm5F, INS-1E cells, and isolated mouse islets. [39][40][41][42] Execution of apoptosis was evident from a slight increase in caspase 3/7 activity after 72 h exposure which has also been observed in hyperglycemia treated INS-1 cells and isolated human islets. 43,44 In conclusion, this study has demonstrated multiple effects of glucotoxicity on gene expression and insulin secretory function in 1.1B4 cells, suggesting that this novel human-derived pancreatic β-cell line is useful for further investigations of β-cell dysfunction and its correction with novel therapeutic agents.…”
Section: Discussionmentioning
confidence: 92%
“…38 We observed that % tail DNA significantly increased in hyperglycemia treated 1.1B4 cells, which is similar to observations with RINm5F, INS-1E cells, and isolated mouse islets. [39][40][41][42] Execution of apoptosis was evident from a slight increase in caspase 3/7 activity after 72 h exposure which has also been observed in hyperglycemia treated INS-1 cells and isolated human islets. 43,44 In conclusion, this study has demonstrated multiple effects of glucotoxicity on gene expression and insulin secretory function in 1.1B4 cells, suggesting that this novel human-derived pancreatic β-cell line is useful for further investigations of β-cell dysfunction and its correction with novel therapeutic agents.…”
Section: Discussionmentioning
confidence: 92%
“…In addition it has been related to chronic glucose stimulation, as seen in an insulinoma cell model, and in diabetes type II [24].…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins found to be differentially expressed, CRABP-1 was already shown to exhibit a differential expression level between control and INS-1E cells submitted to high glucose concentration (4). This was also the case for other fatty acid metabolism-related proteins, giving predominance to a link between glucotoxicity and fatty acid metabolism.…”
Section: Modification Of Isg Proteome By Prolonged High Glucosementioning
confidence: 86%
“…However chronic hyperglycemia is not involved in the initiation of T2D but is rather implicated in the worsening of the pathology. Notably, in recent years, the notion of"glucotoxicity " has emerged to describe the toxic effects of glucose (2)(3)(4)(5). Glucotoxicity exerts deleterious effects on ␤-cells, leading to the increase of apoptosis and therefore the decrease of ␤-cells mass observed in T2D pathology (6 -8).…”
Section: Type 2 Diabetes (T2d)mentioning
confidence: 99%
See 1 more Smart Citation